Navigating complexity, diversity and dynamism: reflections on research for natural resource management - McDougall, C.; Braun, Ann R. (Routledge, 2003)
This chapter seeks to address the apparent tensions that have arisen between ‘traditional’ and ‘participatory’ research approaches in natural resource management research. It does so not only by exploring the relative strengths and weaknesses of these approaches, but also by underscoring the complexity and dynamism inherent in human and natural systems that NRM research addresses. The chapter argues that the desired improvements in natural resource management demand that research institutions asses, more explicitly and thoughtfully than ever before, the multiple facets of traditional and participatory research approaches and consciously craft appropriate and innovative combinations of approaches for each research initiative.